Morphological variation and reproductive incompatibility of three coconutmiteassociated populations of predatory mites identified as Neoseiulus paspalivorus ( Acari: Phytoseiidae) - Sourassou, N.F.; Hanna, R.; Zannou, I.; Moraes, G. de; Negloh, K.; Sabelis, M.W. (Springer, 2011)
Predatory mites identified as Neoseiulus paspalivorus DeLeon (Phytoseiidae) have been considered as agents for classical biological control of the coconut mite, Aceria guerreronis Keifer (Eriophyidae), in Africa and elsewhere. Preliminary identification of geographically distinct populations as belonging to the same species (N. paspalivorus) was based on their morphological similarity. However, laboratory studies recently conducted have shown large differences in feeding behaviors and biological characteristics among individuals collected from three geographic origins: Brazil (South America), Benin and Ghana (West Africa). As morphologically similar specimens do not necessarily belong to the same species, we evaluated under laboratory conditions, reproductive compatibility between the specimens from three geographic locations to ascertain their conspecificity. Morphological measurements were also made to determine whether there is a means of discriminating between them. Inter-population crosses showed complete reproductive isolation between the three geographic populations, but interpopulation discontinuities in morphometric characters were absent. These results indicate that the tested specimens are distinct biological entities despite morphological similarity. Further molecular genetic studies are therefore proposed, including screening for endosymbionts and assessment of genetic differentiation, to determine the cause of reproductive incompatibility and to clarify the taxonomic relationship between those populations.